(20-2x)*(20-2x)=0

Simple and best practice solution for (20-2x)*(20-2x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (20-2x)*(20-2x)=0 equation:



(20-2x)(20-2x)=0
We add all the numbers together, and all the variables
(-2x+20)(-2x+20)=0
We multiply parentheses ..
(+4x^2-40x-40x+400)=0
We get rid of parentheses
4x^2-40x-40x+400=0
We add all the numbers together, and all the variables
4x^2-80x+400=0
a = 4; b = -80; c = +400;
Δ = b2-4ac
Δ = -802-4·4·400
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:
$x=\frac{-b}{2a}=\frac{80}{8}=10$

See similar equations:

| x-8(x-2)=28-5x | | x/5-1/3=2/15 | | 2/3b+5=20-b | | F(2)=5^n | | 3+3=-2(3x-3) | | 8x+3(2x-4)=3(x-6) | | 7=p+10 | | 6/b=8/3 | | -3n-21=-18 | | 6.6x+9.8=16.1x+9.8 | | 6(1-8r)=-7r+6 | | J(×)=2x+9 | | .14=3x-2 | | 5x-6+x+2=-5x+6-15 | | 2w^2+21w+10=0 | | 8(6x+10)=-8 | | 65=9x+6 | | 17x+14+4x=-2 | | m-10=28 | | 3(y+8)=4(y-4 | | 3p^2-47p-16=0 | | 14x=x-17 | | 4(2x+8)=-13+29 | | -3/8h=6 | | -123=3-6(2k+5 | | -17+7x=31+10x | | 228=19r | | 6x-13=4x+2x | | 24+3x9x=x | | p=1=-4 | | (9x+3)+114=180 | | –9s+7=7−9s |

Equations solver categories